Increased Cell–Cell Coupling Increases Infarct Size and Does not Decrease Incidence of Ventricular Tachycardia in Mice - Prestia, Kevin A.; Sosunov, Eugene A.; Anyukhovsky, Evgeny P.; Dolmatova, Elena; Kelly, Caitlin W.; Brink, Peter R.; Robinson, Richard B.; Rosen, Michael R.; Duffy, Heather S. (Frontiers in Physiology, 2011)
Increasing Connexin43 (Cx43) gap junctional conductance as a means to improve cardiac conduction has been proposed as a novel antiarrhythmic modality. Yet, transmission of molecules via gap junctions may be associated with increased infarct size. To determine whether maintaining open gap junction channels impacts on infarct size and induction of ventricular tachycardia (VT) following coronary occlusion, we expressed the pH- and voltage-independent connexin isoform Connexin32 (Cx32) in ventricle and confirmed Cx32 expression. Wildtype (WT) mice injected with adenovirus-Cx32 (Cx32inj) were examined following coronary occlusion to determine infarct size and inducibility of VT. There was an increased infarct size in Cx32inj hearts as compared to WT (WT 22.9% +/- 4%; Cx32inj 44.3% +/- 5%) (p<0.05). Programmed electrical stimulation showed no difference in VT inducibility in WT and Cx32inj mice (VT was reproducibly inducible in 55% of shams and 50% of Cx32inj mice (p> 0.05). Following coronary occlusion, improving cell-cell communication increased infarct size, and conferred no antiarrhythmic benefit.